What platforms and editors need (Pubmet, 2023)
The CRAFT-OA project (Creating a Robust Accessible Federated Technology for Open Access) aims to improve the conditions for publishing open access (OA) diamond journals. CRAFT-OA involves a consortium of 23 partners from 14 European countries, all of whom are engaged in institutional publishing and its infrastructures, and committed to sustaining and developing capacities in the field. Over the course of 36 months, CRAFTOA will deliver technical and community tools, training events, training materials, information, and services for the Diamond OA institutional publishing environment. It will also foster communities of practice with the capacity to sustain the project improvements over time.Within the framework of the EU project CRAFT-OA, we are conducting ten semistructured interviews with institutional platform service providers and editors of scientific journals across Europe. The interviews are a supplement to the quantitative DIAMAS survey and are designed as guided interviews, so that detailed answers and clarifications are possible. The content covers topics such as hosting, submissions and reviews, production, metrics, indexing, archiving, finance, and quality management.The non-representative interviews offer in-depth insights into the needs of editors and platform service providers. The thematic evaluation of the interview will allow us to incorporate the concrete needs and problems of the editors and platform operators into the CRAFT-OA project to improve the conditions for publishing OA diamond journals.During the PUBMET conference, we will be able to present the first results of our interviews and outline trends in the needs of publishing platforms and editors. The detailed analysis is still pending, but a first review shows that indexing, financing and the production of certain formats pose the most problems for both platform operators and publishers.